ADAPTIVE MODE OF THE MSS BTA - Chountonov, G. A.; Najdenov, I. D. (Одеські астрономічні публікації, 2008)
The study of instability of the Main stellar spectrograph of the 6-m Telescope together with system of registration of a spectrum by means of the CCD shows that there is a drift of a spectrum along a dispersion, corresponding to the tenth of a pixel (the hundredth part of Α) in an hour. To eliminate this drift, i.e. to keep a spectrum from displacement, the plane-parallel glass plate was installed behind a slit of the spectrograph. The angle of inclination of this plate changes depending on a mismatch of positions of the current and comparison basic spectra. A lamp of hollow cathode is used. The scheme of this device is described. The results of tests are presented. The time of correction takes about one minute that allows to keep the position of the ThAr spectrum within +-0.0006 Α.